2012
DOI: 10.1016/j.ejps.2011.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel in tyrosine-derived nanospheres as a potential anti-cancer agent: In vivo evaluation of toxicity and efficacy in comparison with paclitaxel in Cremophor

Abstract: Paclitaxel (PTX) has gained widespread clinical use yet its administration is associated with significant toxicity. In the present study, the toxicity and anti-tumor efficacy of tyrosine-derived nanospheres (NSP) for the delivery of PTX was compared to a clinical formulation of PTX in PBS-diluted Cremophor® EL (PTX–CrEL-D). Maximum tolerated dose was determined using a concentration series of PTX in NSP and CrEL-D, with toxicity assessed by measuring changes in body weight. Healthy mice administered PTX–NSP co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 68 publications
2
31
0
Order By: Relevance
“…It is noteworthy that we have achieved significant anti-cancer efficacy with low dose of PTX (10 nM) in our current in vitro combination therapy, whereas we have used 10 times more PTX (100 nM) to achieve significant anti-cancer efficacy in a previous combination therapy in animals (George et al, 2009). Use of high dose of PTX in cancer therapy in animals has been associated with severe side effects (Sheihet et al, 2012) and high mortality rates (Vassileva et al, 2007). Adverse events are also most frequently observed in cancer patients after treatment with high dose of PTX (van Herpen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that we have achieved significant anti-cancer efficacy with low dose of PTX (10 nM) in our current in vitro combination therapy, whereas we have used 10 times more PTX (100 nM) to achieve significant anti-cancer efficacy in a previous combination therapy in animals (George et al, 2009). Use of high dose of PTX in cancer therapy in animals has been associated with severe side effects (Sheihet et al, 2012) and high mortality rates (Vassileva et al, 2007). Adverse events are also most frequently observed in cancer patients after treatment with high dose of PTX (van Herpen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These nanospheres form strong complexes with hydrophobic molecules, as demonstrated using the model compound DAF, and clinically used antitumor agent paclitaxel, a powerful chemotherapeutic drug [28]. In contrast, TyroSpheres do not strongly associate with hydrophilic compounds such as fluorescein [29,30]. Batheja et al demonstrated that a gel formulation of TyroSpheres loaded with Nile red (a hydrophobic model drug) significantly enhanced skin permeation (1.4–1.8 fold) compared to an aqueous dispersion of Nile red-loaded TyroSpheres, both in vitro and in vivo [31].…”
Section: Nanoparticles For Topical Therapymentioning
confidence: 99%
“…Batheja et al demonstrated that a gel formulation of TyroSpheres loaded with Nile red (a hydrophobic model drug) significantly enhanced skin permeation (1.4–1.8 fold) compared to an aqueous dispersion of Nile red-loaded TyroSpheres, both in vitro and in vivo [31]. As these TyroSpheres are suitable only for hydrophobic drugs, they have been extensively studied for the binding and delivery of various therapeutic agents that are hydrophobic and water-insoluble, for example curcumin (unpublished data), cyclosporine A [32], sildenafil [33], rolipram [34] and paclitaxel [30,35,36]. Moreover, these nanospheres are stable for about 6 months, after which time they degrade, most likely through hydrolysis of their ester bonds [28].…”
Section: Nanoparticles For Topical Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…According to the recent literature, nanospheres have been already introduced as a versatile platform that can be adopted for anticancer drugs and target specific applications and have the potential to be combined with the clinically emerging method of targeted therapy (Sheihet et al, 2012;Bushman et al, 2013). Open-ended, multi-wall carbon nanotubes (CNTs) with magnetic nanoparticles encapsulated within their graphitic walls were fabricated for biomedical and pharmaceutical applications (Pagona & Tagmatarchis, 2006;Spitalsky et al, 2009;Vermisoglou et al, 2011) (Figure 1).…”
Section: Drug Delivery Systemsmentioning
confidence: 99%